Handbook on inequalities in sentencing and corrections among marginalized populations
1 online resource (xiv, 276 pages)
Keywords: "The Handbook on Inequalities in Sentencing and Corrections among Marginalized Populations offers state-of-the-art volumes on seminal and topical issues that span the fields of sentencing and corrections. The volume is a comprehensive and fresh approach to examining sentencing and community and institutional corrections. The book includes empirical and theoretical essays and recent developments on the pressing concerns of persons of traditionally non-privileged statuses, including racial and ethnic minorities, indigenous populations, gender, immigrant status, LGBTQ+, transgender, disability, aging, veterans, and other marginalized statuses. The handbook considers a wide range of perspectives for understanding the experiences of persons who identify as a member of a traditionally marginalized group. This volume aims to help scholars and graduate students by providing an up-to-date guide to contemporary issues facing corrections and sentencing. It will also assist practitioners with resources for developing socially informed policies and practices. This collection of essays contributes to the knowledge base by summarizing what is known in each area and identifying emerging areas for theoretical, empirical, and policy work. This is Volume 7 of The ASC Division on Corrections and Sentencing Handbook Series. The handbooks provide in-depth coverage of seminal and topical issues around sentencing and corrections for scholars, students, practitioners, and policymakers"--